Communication ethics in the book of Adabul Mufrad by Imam Al-Bukhari - Subhan Afifi; Noor Akhmad Setiawan (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2021)
This paper aims to explore the notion of communication ethics in the Book of Adabul Mufrad by Imam Al-Bukhari. This study used an interpretive paradigm of qualitative text analysis methods by making Hadith as the text to be analyzed. The units of analysis are the texts of Hadith, which were examined closely for the patterns, models, and communication issues contained in them. The selection criteria for the Hadith selected for analysis included: Ethics regarding the communication process, including an explanation of Ethics in speech, and containing specific prohibitions in the communication process. Based on these criteria, 20 hadiths to be analyzed were selected. The results showed four patterns of ethical communication relationships in 20 hadiths chosen in the book of Adabul Mufrad by Imam Al-Bukhari, namely: (1) Relationships with fellow humans in general, (2) Parent-Child Relations, (3) Relationships with neighbors; and (4) Master-Servant Relationship. Furthermore, communication ethics in all forms of relationships showed five communication ethics patterns: (1) monotheism communication, (2) advice communication, (3) compassion communication, (4) communication without discrimination, and (5) communication without insulting. This paper highlights the ethics of Islamic communication as the ethical basis for the communication process in various human communication contexts. The ethical principles of Islamic communication open the entry of missing behavioral aspects of communication-based on religious values. This paper also provides the necessary theoretical framework for including religiosity and divine guidance in communication ethics.